Systematic review of team performance in minimally invasive abdominal surgery. Issue 3 (30th January 2019) - van der Vliet, W J; Haenen, S M; Solis-Velasco, M; Dejong, C H C; Neumann, U P; Moser, A J; Dam, R M
Abstract: Background: Adverse events in the operating theatre related to non-technical skills and teamwork are still an issue. The influence of minimally invasive techniques on team performance and subsequent impact on patient safety remains unclear. The aim of this review was to assess the methodology used to objectify and rate team performance in minimally invasive abdominal surgery. Methods: A systematic literature search was conducted according to the PRISMA guidelines. Studies on assessment of surgical team performance or non-technical skills of the surgical team in the setting of minimally invasive abdominal surgery were included. Study aim, methodology, results and conclusion were extracted for qualitative synthesis. Results: Sixteen studies involving 677 surgical procedures were included. All studies consisted of observational case series that used heterogeneous methodologies to assess team performance and were of low methodological quality. The most commonly used team performance objectification tools were 'construct'- and 'incident'-based tools. Evidence of validity for the assessed outcome was spread widely across objectification tools, ranging from low to high. Diverse and poorly defined outcomes were reported. Conclusion: Team demands for minimally invasive approaches to abdominal procedures remain unclear. The current literature consists of studies with heterogeneous methodology and poorly defined outcomes. Graphical Abstract: The influence of minimally invasive techniques on team performance and subsequent impact on patient safety remains unclear. The aim of this review was to assess the methodology used to objectify team performance in minimally invasive abdominal surgery and explore demands unique to minimally invasive techniques. Low-quality evidence suggests that a minimally invasive versus open technique appears to have no effect on direct (operating time, severity and frequency of disruptions of workflow) and indirect (patient morbidity and mortality) performance metrics. A set of methodological criteria to improve assessment of surgical team performance and demands relative to surgical techniques is proposed. Team performance in mini-invasive abdominal surgery